2012
DOI: 10.1258/ijsa.2012.012074
|View full text |Cite
|
Sign up to set email alerts
|

Topical imiquimod 5% as a treatment for localized genital Kaposi's sarcoma in an HIV-negative man: a case report

Abstract: We report a case of Kaposi's sarcoma (KS) in an HIV-negative man who has sex with men (MSM) that was successfully treated by topical application of imiquimod 5% cream (Aldara). Our case highlights a potentially effective and non-invasive method of treatment of Kaposi's sarcoma in the shortest timeframe yet recorded. The location of the lesions on the patient's penis also highlights the need for a non-invasive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…If this reactivation leads to virus release, this in turn may stimulate tissue and tumor-resident antigen presenting cells [125]. At this point several cases of skin KS responding to topical treatment with imiquimod have been published, as have been treatment failures [126128]. A systemic clinical trial has not been conducted.…”
Section: Update On Treatment Approachesmentioning
confidence: 99%
“…If this reactivation leads to virus release, this in turn may stimulate tissue and tumor-resident antigen presenting cells [125]. At this point several cases of skin KS responding to topical treatment with imiquimod have been published, as have been treatment failures [126128]. A systemic clinical trial has not been conducted.…”
Section: Update On Treatment Approachesmentioning
confidence: 99%
“…It has been found to be highly effective against KS in some case reports in the literature. [9][10][11][12][13][14][15][16][17] There is only 1 trial wherein imiquimod in KS was investigated for its antitumour activity, showing antitumour activity in 8 of 17 patients. 2 Our study is designed to evaluate the effect of imiquimod, which is distinguished from other local treatment methods by its at-home application, on classic KS lesions compared with cryotherapy, which is one of the most-used treatment methods for KS in our department.…”
Section: Introductionmentioning
confidence: 99%
“…87,88 Case reports have shown that imiquimod cream can be safe and effective in some patients with classic or transplant-associated Kaposi sarcoma. [89][90][91][92][93][94] In a single-center, open-label, phase I/II trial, 17 HIV-negative patients with Kaposi sarcoma received imiquimod 5% cream 3 times per week for 24 weeks. 95 The response rate was 47%.…”
Section: Topical Therapiesmentioning
confidence: 99%